2021
DOI: 10.3389/fimmu.2021.682627
|View full text |Cite
|
Sign up to set email alerts
|

B7-H7 Is Inducible on T Cells to Regulate Their Immune Response and Serves as a Marker for Exhaustion

Abstract: The discovery of immune checkpoints highlights the complexity of T cell signalling during an immune response. Upon activation, T cells express several molecules to regulate their function and to prevent overactivation. B7 homolog 7 (B7-H7) is expressed in tumours and associated with a worse prognosis. However, conflicting data regarding its function suggest that it can be both stimulatory and inhibitory. In this study we report that B7-H7 is also expressed on T cells upon cross-linking of CD3 and CD28 and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The aberrant highly expressed B7 members were correlated with poor prognosis in AML [ 12 ], and the PD-1 expression in CD8 + T cells was independently predictive of poor overall survival and event-free survival in AML patients [ 32 ]. Accordingly, induced expression of B7-H1 and B7-H7 on U937/Ara-C may dampen NK and T-cell function [ 34 36 ]. Moreover, B7-H1 on tumors also interacts with CD80 on T cell, inhibiting T cell responses in vivo [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant highly expressed B7 members were correlated with poor prognosis in AML [ 12 ], and the PD-1 expression in CD8 + T cells was independently predictive of poor overall survival and event-free survival in AML patients [ 32 ]. Accordingly, induced expression of B7-H1 and B7-H7 on U937/Ara-C may dampen NK and T-cell function [ 34 36 ]. Moreover, B7-H1 on tumors also interacts with CD80 on T cell, inhibiting T cell responses in vivo [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al noted that as a suppressive immune checkpoint molecule, HHLA2 blocks the proliferation of CD4 and CD8 T cells and the synthesis of cytokines such as IFN-γ, TNF-α, IL-5, and IL-10 [ 138 ]. Recent studies have shown that HHLA2 is induced to be expressed only when T cells are activated and is preferentially expressed on CD8 T cells after activation, which may be related to the fact that HHLA2 can inhibit the cytotoxic effects of CD8 T cells faster and more strongly [ 141 ]. HHLA2/CD28H has been established to activate human T cells and generate cytokines including IFN-γ, TNF-α, IL-5, and IL-10 through the AKT pathway [ 137 ].…”
Section: Hhla2mentioning
confidence: 99%
“…The function of HHLA2 as a suppressive and stimulatory immune checkpoint in TME may be related to the predominance of different receptor interactions in different cancer types. Intriguingly, one study suggested that HHLA2 may be a better marker of T cell exhaustion than PD-1 [ 40 , 141 ].…”
Section: Hhla2mentioning
confidence: 99%
“…B7H7 exhibits both co-inhibitory and co-stimulatory properties on T lymphocytes [29]. In a study by Luu et al, it has been shown that B7H7 has a predominant expression by exhausted cytotoxic T lymphocytes (CTLs) and T helper 1 cells, which have impaired production of Tumor necrosis factor (TNF)-α and IFN-γ production [30]. In another study on NK-92MI and Jurkat T cells, it was revealed that an alternative receptor for B7H7 on T cells and NK cells is KIR3DL3 (Killer Cell Immunoglobulin Like Receptor), a protein containing three Ig domains with a long cytoplasmic tail.…”
Section: Introductionmentioning
confidence: 99%